Qualisys - optical motion capture (2007)
Qualisys is a leading, global provider of products and services based on optical motion capture. The measurement systems consist of high speed, precision motion capture cameras and advanced software for tracking and analysis of motion data. The core technology of Qualisys products has been developed in Sweden since 1989. The experienced Qualisys staff has created a unique platform for optical motion capture, built to medical and industrial standards. Qualisys is located in the central part of the Gothenburg harbor area, close to the beautiful archipelago of the Swedish west coast. Gothenburg is Sweden`s largest merchant and industrial city, with many high technology companies. Qualisys has a long track record as a supplier of high quality motion capture products and can offer the end user products that provide optimum price/performance.